Analysis of the Content and Recommendations for the Application of FSBU 4/2023 “Accounting (Financial) Reporting” - V. S. Zaika (Учёт. Анализ. Аудит, 2024)
The Ministry of Finance of the Russian Federation has approved a new Federal Accounting Standard (FSBU) 4/2023 “Accounting (Financial) Reporting”. The purpose of the article is to analyze the content of the standard from the standpoint of the theory and practice of forming accounting (financial) statements and to prepare conclusions and proposals based on the results of this work. The study used general scientific methods, such as analysis, comparison, generalization, and specification, and also compared Federal Accounting Standard 4/2023 with the current documents regulating accounting in the Russian Federation, international financial reporting standards, and previously prepared drafts of the federal standards. Based on Federal Accounting Standard 4/2023, the author’s conclusions are formulated both regarding the composition and content of the information disclosed in the forms of accounting (financial) statements, and the procedure for preparing the latter and the conditions for its reliability, not specified in the text of the standard and the information message of the Ministry of Finance of Russia. The article reflects the shortcomings of the new standard, including in terms of the objectives of accounting (financial) statements and the purpose of financial information. The ambiguities of Federal Accounting Standard 4/2023 were eliminated and recommendations for its application were proposed. The results of the study can be applied in the theory and practice of accounting and the formation of accounting (financial) statements.